2023
DOI: 10.1101/2023.07.18.23292814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of and risk factors for peripheral artery disease in rural South Africa: A cross-sectional analysis of the HAALSI cohort

Abstract: Introduction. The burden of peripheral artery disease (PAD) is increasing in low- and middle-income countries. Existing literature from sub-Saharan Africa is limited and lacks population-representative estimates. We estimated the burden and risk factor profile of PAD for a rural South African population. Methods. We used data from 1,883 participants of the HAALSI cohort of South African adults aged 40-69 years with available ankle-brachial index (ABI) measurements. We defined clinical PAD as ABI ?0.90 or >1… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It is well established that the cardiovascular risk increases with age and advanced age is considered as a factor independently linked to PAD in several studies. The study conducted at the emergency department of the Melbourne University Hospital showed that the prevalence of PAD increased significantly with age (25.7% [95% CI: 17.0-36.7]) [26]. The ELLIPSE study showed using a multivariate analysis that advanced age ≥ 81 years was an independent factor of PAD with an OR of 1.45 [27].…”
Section: Pad and Agementioning
confidence: 99%
“…It is well established that the cardiovascular risk increases with age and advanced age is considered as a factor independently linked to PAD in several studies. The study conducted at the emergency department of the Melbourne University Hospital showed that the prevalence of PAD increased significantly with age (25.7% [95% CI: 17.0-36.7]) [26]. The ELLIPSE study showed using a multivariate analysis that advanced age ≥ 81 years was an independent factor of PAD with an OR of 1.45 [27].…”
Section: Pad and Agementioning
confidence: 99%